Abiraterone in patients with recurrent epithelial ovarian cancer: principal results of the phase II Cancer of the Ovary Abiraterone (CORAL) trial (CRUK – A16037). (December 2020) - Banerjee, Susana; Tovey, Holly; Bowen, Rebecca; Folkerd, Elizabeth; Kilburn, Lucy; McLachlan, Jennifer; Hall, Marcia; Tunariu, Nina; Attygalle, Ayoma; Lima, Joao Paulo Da Silveira Nogueira; Perry, Sophie; Chatfield, Peter; et al.
Background: Recurrent epithelial ovarian cancer (EOC) remains difficult to treat, with an urgent need for more therapy options. Androgens bind to the androgen receptor (AR), commonly expressed in EOC. CYP17 inhibitor abiraterone irreversibly inhibits androgen biosynthesis. The Cancer of the Ovary Abiraterone (CORAL) trial was designed to evaluate the clinical activity of abiraterone in EOC. Patients & Methods: CORAL was a multi-centre, open-label, non-randomised, 2-stage phase II clinical trial. Eligible patients had progression within 12 months of last systemic therapy and no prior hormonal anti-cancer agents. Patients received abiraterone 1000 mg daily plus 5 mg prednisone until progression. The primary endpoint was objective response rate (ORR) according to combined Response Evaluation Criteria in Solid Tumours/Gynaecological Cancer Intergroup (RECIST/GCIG) criteria at 12 weeks. Secondary endpoints included clinical benefit rate (CBR) at 12 weeks. Results: A total of 42 patients were recruited; median age 65 (range 34–85) years; 37 (88.1%) had high-grade serous tumours; 20 (48%) had at least three prior lines of therapy; 29/40 (72.5%) were AR+. In stage 1, 1/26 response was observed (in an AR+, low-grade serous EOC); response lasted 47 weeks. Overall, 12 week ORR was 1/42 (2%), CBR was 11/42 (26%) (8/29 (28%) in AR+ patients). Disease control was ⩾6 months for 4/29 (14%). One patient (AR+, low-grade serous) had a RECIST response at 82 weeks. Four (10%) had grade ⩾3 hypokalaemia; 11 (26%) had dose delays. Conclusions: CORAL represents the first trial of an AR targeted agent in ovarian cancer. While responses were rare, a subset of patients achieved sustained clinical benefit. Targeting AR in EOC including low-grade serous cancer warrants further investigation. Trial registration: CORAL is registered on the ISRCTN registry: ISRCTN63407050;http://www.isrctn.com/ISRCTN63407050